Getting smaller: size dynamics of employer enterprises in Portugal - Sarmento, Elsa (2011)
From 1985 to 2007, by applying to the Quadros de Pessoal dataset the methodology and definitions of the OECD/Eurostat Manual on Business Demography Statistics. We observe that firm size has been decreasing in Portugal over all broad sectors, regions and entrants and exiters from the market and also that firm size distribution is right-skewed, envolving over time towards a lognormal distribution.